The price and promise of specialness : the political economy of overseas Chinese policy in the People's Republic of China, 1949-1959 - Lim, Jin Li (Chinese overseas., 2019)
In The Price and Promise of Specialness, Jin Li Lim revises narratives on the overseas Chinese and the People's Republic of China by analysing the Communist approach to 'overseas Chinese affairs' in New China's first decade as a function of a larger political economy. Jin Li Lim shows how the party-state centred its approach towards the overseas Chinese on a perception of their financial utility and thus sought to offer them a special identity and place in New China, so as to unlock their riches. Yet, this contradicted the quest for socialist transformation, and as its early pragmatism fell away, the radicalising party-state abandoned its promises to the overseas Chinese, who were left to pay the price for their difference.